Who cares about esports? - Nicholas T. Taylor (Eludamos)
Meant as both a provocation and a prompt, ‘who cares about esports?’ opens the topic up to critical scrutiny at a time when the esports industry is in the midst of a(nother) serious contraction, even as there is a sizeable jump in the breadth and amount of esports research. As the introduction to this special section on Sustaining Equitable Competitive Gaming, this article considers the interplay of these two transformations, while also opening up a third, vital line of inquiry: ‘who cares for competitive gaming?’ This question is meant, on the one hand, to underscore the difference—and the relationship—between competitive gaming and esports, while also providing an overview of the kinds of critical and timely care documented by the four articles in this special section.